2012
DOI: 10.1016/j.chembiol.2012.03.012
|View full text |Cite
|
Sign up to set email alerts
|

A Nonpeptidic Cathepsin S Activity-Based Probe for Noninvasive Optical Imaging of Tumor-Associated Macrophages

Abstract: SUMMARY Macrophage infiltration into tumors has been correlated with poor clinical outcome in multiple cancer types. Therefore, new tools to image tumor-associated macrophages could be valuable for diagnosis and prognosis of cancer. Herein we describe the synthesis and characterization of a cathepsin S-directed, quenched activity-based probe (qABP), BMV083. This probe makes use of an optimized non-peptidic scaffold leading to enhanced in vivo properties relative to previously reported peptide-based probes. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 31 publications
5
88
0
1
Order By: Relevance
“…When we analyzed the labeling pattern by in-gel fluorescence, we observed that only CatS retained activity upon CQ treatment, consistent with prior reports that CatS is capable of retaining activity at neutral pH (V. Turk et al, 2012; Verdoes et al, 2012) (Figure 4D). We also analyzed these samples by western blot to confirm loading (Figure 4D) and cathepsin protease expression.…”
Section: Resultssupporting
confidence: 89%
“…When we analyzed the labeling pattern by in-gel fluorescence, we observed that only CatS retained activity upon CQ treatment, consistent with prior reports that CatS is capable of retaining activity at neutral pH (V. Turk et al, 2012; Verdoes et al, 2012) (Figure 4D). We also analyzed these samples by western blot to confirm loading (Figure 4D) and cathepsin protease expression.…”
Section: Resultssupporting
confidence: 89%
“…Indeed, when we compared the labeling profiles of the prior probe BMV083 to the new BMV117 probe in live RAW 264.7 cells (mouse leukemic monocyte macrophage cell line) we found that BMV117 showed exclusive labeling of cathepsin S, whereas BMV083 also labeled a substantial amount of cathepsin B and, at higher concentrations, cathepsin L (Figure 1b and Figure S1A). 8 However, the gain in selectivity by introducing increased steric bulk in the P2 position came at the cost of a 10-fold decrease in potency towards cathepsin S. We recently reported the optimized near-infrared pan-reactive cysteine cathepsin qABP BMV109 that contains a more reactive phenoxymethyl ketone (PMK) electrophile (also known as the “warhead”), a shorter spacer and a more hydrophilic sulfo-QSY21 quencher. This probe targets a broad panel of cysteine cathepsin targets and has better aqueous solubility and improved in vivo properties compared to the previous generation acyloxymethyl ketone (AOMK) probes.…”
Section: Resultsmentioning
confidence: 99%
“…Eight hours after treatment, mice were euthanized and perfused with PBS, and samples of heart, liver, lung, spleen, pancreas, and kidney were collected and frozen in liquid nitrogen. Organs were lysed in citrate buffer, and cathepsin activity was measured as previously described (34,35). Briefly, 50 μg of protein lysate was labeled for 1 h at room temperature with a mixture of 1 μM FY01 and 1 μM DCG04, and run on an SDS/PAGE gel.…”
Section: Methodsmentioning
confidence: 99%